Aplicação da moringa oleífera no tratamento de água com turbidez - Lima, Niedja Maria de (2015)
One of the greatest challenges for science is searching for methodological processes which reflect directly or indirectly in the environment, decreasing the environmental impact and at the same time, providing the development of these processes. Water is currently one of those challenges, especially with regard to the availability and the pattern of physical-chemical and microbiological quality for consumption. Because of this problem, is that the work aims using moringa seeds to reduce turbidity, by presenting a biological coagulant that has advantages, when compared with the chemical coagulants. The water was collected in the Capibaribe River, in the municipality of Recife, Pernambuco, Brazil. The physical and chemical parameters such as pH, electrical conductivity and turbidity were determined before (pH=8 .11; CE=8.35 mS/cm; turbidez= 16.62 NTU) and after treatment. The Moringa powder oleifera were 0, 50, 100, 200, 250 and 300 mg/200mL of water, related to contact time corresponding to 0.1, 2, 4, and 6:0, which are adjusted for planning experimental CCRD. After the tests, the result obtained in the removal of up to 100 of the turbidity was with the concentration of 200 mg, with the time of sedimentation 2:0, proving the efficiency of biological coagulant present in Moringa seed oleifera for clarifying the water. Before and after the treatments were determined turbidity, pH and electrical conductivity. The results were analyzed by ANOVA table and the chart of Pearson representing respectively a significance level of 5 and correlation between variables. It was found that the time of sedimentation and pH showed correlation of 0.63; turbidity and pH was 0.49. The results observed in the electronic scanning photomicrographs indicate improvement in the particle biological sorvente dissolved.